Inertiamittausyksiköiden ja gps-laitteiden käyttö urheilussa - Hoikkala, Kalle (2018)
The use of GPS and inertial measurement technology in sports have increased due to advances in those technologies. The purpose of these technologies is to provide quantitative data of the performance for the athlete. The goal of this paper to do a literature review on how GPS and inertial measurement technologies are used in sports. Both technologies can provide means for the athlete to enhance performance and prevent injuries in real time. GPS technology has been used to give information about location, velocity, distance and other values that are derived from these values. Inertial measurement technology has among other things been used to measure trajectories, count repetitions and measure forces impacting an athlete. Especially when both these technologies are used together, they can measure a great amount of parameters influencing the performance at the same time. Using the information provided, the athlete can optimize his/her training and enhance his/her performance.